National Seminar on Development Journalism: 19-21 Sha'ban 19-21 1413 / 11-13 February 1993 Kuala Lumpur, Malaysia (American Journal of Islam and Society, 1994)
This seminar, organized by the Asian Institute for DevelopmentCommunication in collabomtion with the Asia Foundation, was attendedby thirty journalists and media professionals from Malaysia. Among theresource persons were Mochtar Lubis (Chairman, Press Foundation ofAsia) and S. M. Ali (Chief Editor, Daily Star, Bangladesh).The seminar was opened by Riley Haji Jeffrey (Deputy Minister ofInformation, Malaysia), who discussed the importance and the need fordevelopment journalism to achieve the goal of Vision 2020 (i.e., becominga fully "developed country" by 2020). He said that "mass mediashould not deprive people of in-depth analysis or exposition of issues inthe social, economic, cultural , and environmental fields." James R. Klein(Representative, Asia Foundation) analyzed the complementary roles ofeditors and journalists in fulfilling the objectives of development journalism.Khairul Bashar (Executive Director, Aidcom) outlined the seminar'sgoal: to offer a forum for senior journalists and media executivesto exchange views, identify issues, and recommend methodologies fortraining in development journalism.The "Satellite Teleconferencing" session, which focussed on investigativeqxxthg, featured an Asian panel of senior journalists and Americanjournalists. This was organized with technical assistance from theUnited States Information Service. The Asian panelists were Philip Matthews,Mochtar Lubis, s. M. Ali, Gamsudin Rahim, and Islami Lustapa.American panelists were Bell Dedman and Jonathan Newman. This paneldiscussed investigative journalism as practiced in the United States andon sharing the norms followed in practicing the same skills in Asia.The panel on "Development Journalism: Challenges and Future Direction"was chaired by Haji A. Samad Ismail (Chairman, Panel of NationalInformation Policy, Malaysia). Participants included Mochtar Lubis, S. M.Ali, Kadir Jasin (Group Editor, New Straits Z'imes, Malaysia), Abdul RahmanSulaiman (Editor-in-Chief, Bernama [Malaysian News Agency]),Haji Mazlan Nordin (Chairman, Bernama), and Samsudin Abdul Rahim(Head, Communication Department, National University of Malaysia).The panel made the following points: development journalism shouldalways portray changes that should be humanized; the process of adjust ...